1984
DOI: 10.1159/000183114
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Nephropathy and Pregnancy

Abstract: We describe 26 pregnancies in 19 patients with lupus nephritis. There were 4 spontaneous abortions, 2 therapeutic abortions, 4 stillbirths and 1 neonatal death. 10 deliverieswere preterm and 2 fetuses were small for gestational age. 8 pregnancies were not accompanied by change of renal symptoms. Mild signs of renal involvement appeared during pregnancy in 4 patients. 6 patients showed an increase in proteinuria already present before pregnancy without renal function deterioration. A moderate worsening of renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(17 citation statements)
references
References 12 publications
0
16
1
Order By: Relevance
“…Poliak's group [32] recorded many years ago that patients with lupus nephri tis are at greatest risk of deterioration in the post-partum period. Renal function may deteriorate at this time in association with other features of intravascular coagula tion such as thrombocytopenia and microangiopathic haemolytic anaemia [33]. Our patients had evidence of intravascular renal thrombi as well as the haematological lesions which accompany such changes namely microan giopathic haemolytic anaemia, thrombocytopenia and raised fibrin degradation products.…”
mentioning
confidence: 50%
“…Poliak's group [32] recorded many years ago that patients with lupus nephri tis are at greatest risk of deterioration in the post-partum period. Renal function may deteriorate at this time in association with other features of intravascular coagula tion such as thrombocytopenia and microangiopathic haemolytic anaemia [33]. Our patients had evidence of intravascular renal thrombi as well as the haematological lesions which accompany such changes namely microan giopathic haemolytic anaemia, thrombocytopenia and raised fibrin degradation products.…”
mentioning
confidence: 50%
“…Hayslett and Lynn [ 16] and Imbasciatti et al [ 18] have both reported in their lupus nephritis series that renal biopsies performed prior to gestation were not predictive of the renal outcome. None of these reports however describe histopathologic changes occurring during preg nancy in women with active lupus nephritis.…”
Section: Discussionmentioning
confidence: 94%
“…In pregnant women with IgA-N, proteinuria might increase or remain unchanged, but it does not just disap pear [2,4], However, a behavior of this kind has been reported (albeit rarely) in pregnant women with lupus ne phritis: Hayslett et al [7] report 2 cases where proteinuria during pregnancy decreased from l.3 and l.l to respectively 0.4 and 0.2 g/24 h, and Imbasciati et al [8] describe 3 patients whose proteinuria decreased during pregnancy (from 4.0, 5.0 and 0.2 to 2.0, 0.5 and 0.1 g/24 h) but was exacerbated in the puerperium (to respectively 12.0,8.8 and 2.1 g/24 h). These data led to the suspicion that our patient may have had an underlying lupus nephritis, but clinical, serological and pathological examinations excluded such a hypothesis.…”
Section: Discussionmentioning
confidence: 99%